(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The article discusses innovative approaches to the formation of professional competence of students at a medical university. Professional competence is considered as an integrative quality of a future specialist, including theoretical knowledge, practical skills, clinical thinking, communication culture, professional responsibility and readiness for continuous self-development. Special attention is paid to problem based learning, the case method, simulation technologies, interactive teaching methods and project-based learning. The article substantiates that the use of innovative pedagogical approaches increases students’ learning motivation, develops independence, practice-oriented thinking and readiness for future professional activity. It is concluded that the systematic introduction of modern teaching methods into the educational process contributes to improving the quality of training of future medical specialists.